New Radiological contributions to low Digestive Tract Bleeding.: Part II - Zubiaurre, Jorge (Cirugía del Uruguay, 1983)
There are two situaions In he radiological study of low digesive ract bleeding: he serious acve bleeding and he stopped or mild leeding.